An educational intervention impact in improving nurses' knowledge of noninvasive ventilation - Gírio, Ricardo (2024)
Background: non-invasive ventilation (NIV) has emerged as a potentially safe and relatively low-cost therapeutic approach for a wide range of respiratory conditions. However, recent evidence shows that the lack of up-to-date and recurrent training in this area is the main obstacle to providing quality care to people in need of NIV. Objective: to assess the impact of an Educational Intervention (EI) on the level of knowledge of nurses in a Post-Anesthesia Care Unit (PACU) in central Portugal. Methodology: quasi-experimental study, without a control group, with pre- and post-intervention evaluation. The EI followed the recommendations proposed by Karim et al. (2019) and included seven hours of theoretical and practical training. Nurses (N = 19) were assessed using a questionnaire previously developed by Palma (2018). Results: between the pre- and post-intervention periods, there was an improvement in performance in terms of knowledge about NIV (84.2%), especially in indications, contraindications, therapeutic goals, possible associated complications, BIPAP modality, interface selection and ventilatory parameters. Conclusion: the developed EI proved to be an effective and positive contribution to the nursing team in a PACU, enhancing evidence-based practice and more effective, timely, and safe nursing care in this field.